Combining cellulose substrates and perovskites in sustainable solar cells is possible: a systematic literature review offering realistic solutions - Valdez García, Joaquín; Hadadian, Mahboubeh; Aggarwal, Vidushi; Yli-Paavola, Sirius; Kaschuk, Joice; Suhonen, Riikka; Välimäki, Marja; Miettunen, Kati (Royal Society of Chemistry (RSC), 2026)
The aim of this article is to provide direction for the advancement of cellulose films as sustainable substrates for perovskite solar cells (PSCs). Cellulose, the most abundant biopolymer on Earth, represents a viable, renewable alternative to glass and synthetic polymers when subjected to appropriate modifications. It can be customized via crosslinking, plasticization, and functionalization to increase flexibility and solvent resistance while decreasing gas permeation, surface roughness, and thermal expansion. The adoption of cellulose can drive transformative changes in PSC processing, facilitating the integration of sustainable electrode materials and greener alternatives to toxic solvents, as well as the replacement of high-temperature treatments. Although the literature contains numerous solutions to specific challenges, these findings are scattered across different fields and must be critically assessed for PSC suitability. In this article, we critically review alternative fabrication methods and form a step-by-step multidisciplinary strategy to alter both cellulose and PSC fabrication protocols for the development of sustainable next-generation solar cells.